New insights into orthostatic hypotension in multiple system atrophy: a European multicentre cohort study. Issue 5 (14th May 2015) - Pavy-Le Traon, A; Piedvache, A; Perez-Lloret, S; Calandra-Buonaura, G; Cochen-De Cock, V; Colosimo, C; Cortelli, P; Debs, R; Duerr, S; Fanciulli, A; Foubert-Samier, A; Gerdelat, A; et al.
Abstract : Objectives: Orthostatic hypotension (OH) is a key feature of multiple system atrophy (MSA), a fatal progressive neurodegenerative disorder associated with autonomic failure, parkinsonism and ataxia. This study aims (1) to determine the clinical spectrum of OH in a large European cohort of patients with MSA and (2) to investigate whether a prolonged postural challenge increases the sensitivity to detect OH in MSA. Methods: Assessment of OH during a 10 min orthostatic test in 349 patients with MSA from seven centres of the European MSA-Study Group (age: 63.6±8.8 years; disease duration: 4.2±2.6 years). Assessment of a possible relationship between OH and MSA subtype (P with predominant parkinsonism or C with predominant cerebellar ataxia), Unified MSA Rating Scale (UMSARS) scores and drug intake. Results: 187 patients (54%) had moderate (> 20 mm Hg (systolic blood pressure (SBP)) and/or > 10 mm Hg (diastolic blood pressure (DBP)) or severe OH (> 30 mm Hg (SBP) and/or > 15 mm Hg (DBP)) within 3 min and 250 patients (72%) within 10 min. OH magnitude was significantly associated with disease severity (UMSARS I, II and IV), orthostatic symptoms (UMSARS I) and supine hypertension. OH severity was not associated with MSA subtype. Drug intake did not differ according to OH magnitude except for antihypertensive drugs being less frequently, and antihypotensive drugs more frequently, prescribed in severe OH. Conclusions: This is the largest study of OH in patients with MSA. Our data suggest that the sensitivity to pick up OH increases substantially by a prolonged 10 min orthostatic challenge. These results will help to improve OH management and the design of future clinical trials.